Numerical investigation the effect of air supply on the biomass combustion in the grate boiler. (February 2019) - Zhou, Anqi; Tu, Yaojie; Xu, Hongpeng; Wenming, Yang; Zhao, Feiyang; Keng Boon, Siah; Subbaiah, Prabakaran
Abstract: The burning behavior of biomass in the industrial-scale grate boiler is investigated through numerical simulation. A dynamic one-dimensional model is developed to simulate the biomass combustion in the grate bed. The three-dimension simulation is also employed to determine the radiation temperature as the boundary condition for the developed model. The model is validated with experimental measurements. The effect of air supply for biomass combustion characteristics in the grate bed is discussed based on the simulation results. It is found that the increase of air supply shortens the burning time and raises the maximum combustion temperature. Under the condition of constant excess air ratio, the fuel can be burnt out in advance by increasing primary air supply, but the radiation temperature in the zone 1 of grate bed is decreased when the ratio of primary air is larger than 43%. Based on these predicted results, the suggested ratio of primary to secondary air is 43:57 for this industrial-scale grate boiler. The effect of primary air flow distribution in different zones is also investigated to reduce the heat loss from bottom ash.